ANALISIS STRATEGI PROMOSI PRODUK TABUNGAN HARI TUA (THT) BALI DWIPA DALAM MENINGKATKAN MINAT MENABUNG NASABAH DI PT BANK PEMBANGUNAN DAERAH BALI CABANG MANGUPURA - Ni Putu Ananda Sintia Mahadewi; I Nyoman Suka Sanjaya; I Ketut Santra (CV. Lafadz Jaya, 2026)
This study aims to describe the promotional strategies implemented for the THT Bali Dwipa Savings product at Bank BPD Bali Mangupura Branch and to describe the role of these promotional strategies in increasing customers' saving interest. This study was conducted because, based on the account opening data for the THT Bali Dwipa Savings product throughout 2025, the number of new customers fluctuated and tended to decline during several periods. Therefore, it is necessary to examine the promotional strategies implemented to increase customers' saving interest. This study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The collected data were then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the promotional strategies implemented included advertising, sales promotion, personal selling, public relations, and direct marketing. These strategies were carried out through social media, brochures, WhatsApp, telephone communication, socialization and financial literacy activities, the distribution of gifts or souvenirs, as well as direct communication with prospective customers. The promotional strategies played a role in increasing customers' saving interest by helping the public obtain information about the THT Bali Dwipa Savings product, understand its benefits, and consider opening an account. In addition, recommendations from family members and friends also contributed to the interest of some customers in choosing the THT Bali Dwipa Savings product.